Design of a Koch-Curved LPDA Antenna With Optimized Beamwidth to Improve the Aperture Efficiency of Reflector Antennas - Jiyoung Park; Changhyeon Im; Hosung Choo (IEEE Access)
In this paper, we propose a Koch-curved log-periodic dipole array (LPDA) antenna with wideband characteristics and an optimal beamwidth as a reflector feed antenna for SIGINT satellites. Koch-curved dipole elements are employed to improve aperture efficiency by adjusting the beamwidth. The beamwidth is adjusted by changing the angle and size of the Koch-curve applied to the dipole array elements. Additionally, a tapered line boom is applied to improve the matching characteristics. The performance of the proposed antenna such as the reflection coefficients and radiation pattern characteristics are measured in an anechoic chamber. The proposed antenna shows a reflection coefficient of less than −8 dB over a wideband from 2.1 GHz to 8 GHz and an average 8.6 dB beamwidth of 109.6° with an average bore-sight gain of 6.6 dBi. Furthermore, using the proposed feed antenna, an average bore-sight gain of 30.9 dBi is measured from 2 GHz to 6 GHz. The results confirm that the proposed antenna, which has wideband characteristics and an optimized beamwidth across the operating frequency range, is suitable as a reflector feed antenna in the SIGINT satellite application.